Supramolecular Metal Complexes for Imaging and Radiotherapy - Schatz, Jürgen; Schühle, Daniel (Supramolecular Systems in Biomedical Fields, 2013)
Modern medicinal diagnosis strongly relies on imaging techniques. Supramolecular chemistry can help radiologists by enhancing images that are acquired with the help of exogenous contrast agents. Most targeting functions such as peptides, saccharides, antibodies etc. bind to their receptors via non-covalent interactions. When reporter groups are attached to these vectors via linkers, a rather complex supramolecular guest is designed that finds its host in vivo. In these cases, supramolecular chemistry is used to adjust the biodistribution of reporter groups to medical needs. When metal ions are used in imaging, they need to be complexed in most cases in order to control their biodistribution and to make them safe. Macrocycles are common ligands for metal complexation in this field and thus, almost any metal based contrast agent is a supramolecular complex per se. A very efficient tool for “a closer look into the body” is magnetic resonance imaging (MRI). The resolution and specificity of conventional MRI can be enhanced using contrast agents. MRI has very good resolution but it is a rather insensitive technique. A consequence is that targets that are expressed at low concentrations cannot be imaged using MRI. Both nuclear and optical imaging have much higher sensitivity but have the disadvantage of the need of radiation plus lower resolution and very limited deep tissue penetration respectively. In all these techniques, supramolecular chemistry offers possibilities that classical chemistry cannot fulfill. Radioactive metals can also be used to destroy diseased tissue for therapeutic applications—again utilizing supramolecular principle